A three-stage procedure using bone transportation for the treatment of sternoclavicular infectious arthritis. Issue 1 (December 2016) - Chen, Hua; Ji, Xinran; Hao, Ming; Zhang, Qun; Tang, Peifu
Abstract Background Sternoclavicular joint (SCJ) infectious arthritis is a rare disease. A standard treatment for SCJ infection has not been established. This study aimed to assess the clinical outcomes of a three-stage procedure with bone transportation (BT) for treating SCJ infectious arthritis. Methods Six patients (mean age 39.5 years) with chronic SCJ infectious arthritis were included in the study. The patients underwent a three-stage treatment between January 2009 and December 2012, and results were analyzed retrospectively. Following debridement, immediate flap closure was conducted, and BT of the clavicle was performed to fill the gap using a monolateral external fixator. SCJ reconstruction with a tendon autograft was performed, and the external fixator was finally removed. Clinical outcomes were evaluated using Disabilities of the Arm, Shoulder, and Hand (DASH) scores and Constant scores. The average follow-up period was 16 months (range 12–36 months). Results The DASH scores decreased from 53.6 ± 4.9 preoperatively to 24.4 ± 3.1 postoperatively. The Constant scores for pain, activity level, positioning, strength, and range of motion were significantly high after the treatment. The total Constant score improved from 32.5 ± 5.8 preoperatively to 76.7 ± 6.4 postoperatively. All patients were satisfied with the therapeutic effect. No complications occurred. Conclusions The three-stage procedure with BT improves shoulder function and movement and relieves pain. It is an effective and safe method for treating SCJ infectious arthritis.